2022
DOI: 10.3390/life12111779
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone Alleviates Cadmium Induced Stress in Germinated Lens culinaris Seeds by Reducing Oxidative Stress and Increasing Antioxidative Activities

Abstract: This study investigated the effect of thymoquinone on seeds germination and young seedlings of lentils under cadmium (Cd) stress (300 µM). Three different concentrations (10 µM, 1 µM, and 0.1 µM) of thymoquinone were applied. Our results indicated that thymoquinone has a positive effect on several physiological and biochemical parameters on seeds germination and young seedlings of lentils under Cd stress, which led to enhancing their growth. A significant increase in shoot and root length, fresh and dry weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…This significant improvement could reflect the robust antioxidant properties of THQ, which several previous works have evidenced (Hammed and Amao, 2022;Ibrahim et al, 2022). Thenceforth, oxidative impairment of the brain is generated by numerous types of machinery, for instance, higher lipid peroxidation, protein unfolding, fluctuations in pH, mitochondrial disturbance, DNA injury, and the intracellular calcium brought about the elevation of cell death (Ben Mrid et al, 2022). Aboubakr et al (2021) suggested THQ alleviates chlorpyrifos-induced neuronal injury in rats via enhancing the SOD, CAT and GSH and reduced the MDA levels significantly.…”
Section: Testicular Changesmentioning
confidence: 86%
See 2 more Smart Citations
“…This significant improvement could reflect the robust antioxidant properties of THQ, which several previous works have evidenced (Hammed and Amao, 2022;Ibrahim et al, 2022). Thenceforth, oxidative impairment of the brain is generated by numerous types of machinery, for instance, higher lipid peroxidation, protein unfolding, fluctuations in pH, mitochondrial disturbance, DNA injury, and the intracellular calcium brought about the elevation of cell death (Ben Mrid et al, 2022). Aboubakr et al (2021) suggested THQ alleviates chlorpyrifos-induced neuronal injury in rats via enhancing the SOD, CAT and GSH and reduced the MDA levels significantly.…”
Section: Testicular Changesmentioning
confidence: 86%
“…The discrepancy in the antioxidant system is furthermore the reason for MDA. Lipid peroxidation weakens cell membrane and makes it vulnerable to more oxidation by free radicals (Ben Mrid et al, 2022).…”
Section: Testicular Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…A byproduct of the corn starch industry, CSL (corn steep liquor) protein hydrolysate has been shown to significantly increase wheat germination [81]. Thymoquinone (TQ) is a primary bioactive component from black seed oil (Nigella sativa) [82], reported to increase lentil germination and seedling vigor indexes along with alleviation of cadmium stress [83]. Other thyme essential oils were used to coat durum wheat seeds, resulting in enhanced germination and tolerance to drought stress [84].…”
Section: Examples Of the Application Of Plant-based Biostimulants As ...mentioning
confidence: 99%
“…Thymoquinone, the main bioactive ingredient of Nigella sativa essential oil, is known to have important antioxidant, antimicrobial and anti-inflammatory properties [1]. It has also been proven to reduce induced stress in Lens culinaris seeds, making it ideal as a plant biostimulant [2]. Since the next generation of these types of biostimulants should ensure the slow release of the active ingredient due to the phytotoxic effects that are possible at high concentrations, encapsulation in a delivery system, such as through the use of emulsions, yields promising perspectives [3].…”
mentioning
confidence: 99%